Preparation and Evaluation of Xanthan Gum-Based Floating Tablets Bearing Ibuprofen - Singh, Pawan; Junaid, Mohd; Singh, Devendra; Kumar, Mohit (Journal of Neonatal Surgery, 2025)
This study investigates the development and evaluation of floating tablet formulations (F1, F2, F3, and F4) for controlled drug delivery in the gastric environment. The physical properties, floating behavior, and drug release profiles of the tablets were assessed. All formulations exhibited desirable characteristics, including adequate thickness (2.87 ± 0.024 mm to 4.0 ± 0.034 mm), good hardness (4.37 ± 0.03 kg/cm² to 6.0 ± 0.03 kg/cm²), low friability (0.2% to 0.7%), and acceptable weight variation (2.0% to 2.63%), ensuring stability and uniformity. Floating lag time ranged from 60 seconds (F1) to 200 seconds (F4), with all formulations demonstrating sustained buoyancy for over 6 hours, crucial for prolonged gastric retention. The drug release profiles indicated that F1 exhibited the fastest release, with 45.2% of the drug released after 7 hours, followed by F2 (36.7%), F3 (32.9%), and F4 (24.7%). These results suggest that F1 is ideal for rapid drug absorption, while F4 is more suited for controlled release applications. The successful development of these floating tablets with variable release profiles provides flexibility in designing drug delivery systems tailored to specific therapeutic needs. Further optimization may enhance their clinical efficacy in treating conditions requiring prolonged drug release in the stomach.